Efficiency of Earthworm, Eudrilus Eugeniae (Kinberg, 1867) in The Conversion if Orange Peel (Citrus Sinensis) Waste Mixed with Diclofenac Into Compost - Ravi, G.; Kalaivanan, K.; Durairaj, S.; Ramesh, M.K.; Selladurai, G. (International Journal of Scientific Research in Biological Sciences, 2019)
The efficiency of the earthworm Eudrilus eugeniae was studied in the present work where the earthworm was subjected to the conversion of Orange peel waste mixed with diclofenac into compost in the form of micro and macro minerals on 15th and 30th days. Micro and Macro nutrients such as N, P, K and Fe, Mn, Zn, Cu were analyzed in the Orange peel waste and mixed with diclofenac along with control. Similarly physical characteristics were also analyzed to understand the efficiency of earthworm in maintaining the physical status of the soil. The analysis revealed that the P and Fe were increased significantly on 15th and 30th days where as the Physical property i.e., EC was increased only in the orange peel waste conversion where as in the diclofenac contaminated waste, the EC was stable in the present study. The pH was slightly increased on 15th and stable on 30th day. FTIR Study was undertaken to identity the chemical group present in the control and experiment. Histological changes were compared with that of experiment and the efficiency of the earthworm has been understood in the present work within a short period of 15th to 30th days.